Você está na página 1de 10

[1] [2]

[3]

f (x) = 0 f [a, b]

|p N p N1 |

= 0 N

|p N |

< , p N

= 0

p N

f X f X

a b T OL N a b T OL N

p

N − p N − 1 | = 0 N | p N | < ,

N − p N − 1 | = 0 N | p N | < ,
N − p N − 1 | = 0 N | p N | < ,
N − p N − 1 | = 0 N | p N | < ,
N − p N − 1 | = 0 N | p N | < ,

N − p N − 1 | = 0 N | p N | < ,

N − p N − 1 | = 0 N | p N | < ,

N − p N − 1 | = 0 N | p N | < ,
x 3 + 4 x 2 − 10 = 0 [1 , 2] p

x 3 + 4x 2 10 = 0 [1, 2]

x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p

p

x 3 + 4 x 2 − 10 = 0 [1 , 2] p

x 3 + 4 x 2 − 10 = 0 [1 , 2] p

x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p

x 3 + 4 x 2 − 10 = 0 [1 , 2] p
x 3 + 4 x 2 − 10 = 0 [1 , 2] p

  x 3 + 4 x 2 − 10 = 0 [1 , 2]

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 
  x 3 + 4 x 2 − 10 = 0 [1 , 2]

x 3 + 4x 2 10 = 0 [1, 2]

p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −
p = g ( p ) p 0 | p N − p N −

p = g(p) p 0

|p N p N1 | |p N |

< , p N

= 0 p N = 0 N

g X g X

p 0 T OL N p 0 T OL N

p

10 − 4 x 3 + 4 x 2 − 10 = 0 [1 ,

10 4 x 3 + 4x 2 10 = 0 [1, 2] p 0 = 1,5

x = g(x) = (

10 4+x ) 1/2

10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]
10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]
10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]
10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]

10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]
10 − 4 x 3 + 4 x 2 − 10 = 0 [1 , 2]

10 − 4 x 3 + 4 x 2 − 10 = 0 [1 ,

10 4 x 3 + 4x 2 10 = 0 [1, 2] p 0 = 1,5

3 + 4 x 2 − 10 = 0 [1 , 2] p 0 = 1
3 + 4 x 2 − 10 = 0 [1 , 2] p 0 = 1
3 + 4 x 2 − 10 = 0 [1 , 2] p 0 = 1
3 + 4 x 2 − 10 = 0 [1 , 2] p 0 = 1

f (x) = 0 f p 0

|p N p N1 | < , p N

= 0 p N = 0

|p N |

N

f X f X

f X f X

p 0 T OL N p 0 T OL N

p

p 0 T OL N p 10 − 5 x 3 + 4 x 2 −

10 5 x 3 + 4x 2 10 = 0 [1, 2] p 0 = 1,5

p 0 T OL N p 10 − 5 x 3 + 4 x 2 −
p 0 T OL N p 10 − 5 x 3 + 4 x 2 −
p 0 T OL N p 10 − 5 x 3 + 4 x 2 −
p 0 T OL N p 10 − 5 x 3 + 4 x 2 −

10 − 5 x 3 + 4 x 2 − 10 = 0 [1 ,

10 − 5 x 3 + 4 x 2 − 10 = 0 [1 ,
10 − 5 x 3 + 4 x 2 − 10 = 0 [1 ,

10 5 x 3 + 4x 2 10 = 0 [1, 2] p 0 = 1,5